Assessment the Response of Chickpea Genotypes to Agrobacterium -Mediated Transformation System - Ibrahim, Diaa A.; Khatib, Fatih; Baum, Michael (Science Journal of University of Zakho, 2016)
Transformation protocol based on the inoculation of chickpea mature embryos with Agrobacterium suspension was carried out. Four chickpea lines and one Iraqi local variety were used as recipient to the foreign gene of Agrobacterium tumefaciens strain (AgL1). Three plasmids were already inserted in the bacteria cells. The first plasmid carries the bar gene coding for phosphinothricin acetyle transferase (PAT), which confers resistance to the herbicide phosphinothricin or glofosinate ammonium(PPT) and uidA (gusA) gene coding for β-glucuronidase (GUS). The other two plasmids carried the LeEREBP gene which confers drought resistance and bar gene coding for phosphinothricin acetyle transferase (PAT). Successfully regenerated explants were subjected to selection pressure on 10 mg /l of phosphinothricin PPT and the putative transgenic explants were rooted on root induction medium consisting of MS basal medium with B5 medium vitamins supplemented with 2.5 ml of 1mg /ml IBA in addition to grafting on 7 days old non- transformed rootstock. PCR approved transgenic chickpea. 600 mg/l of PPT was used by painting the leaves of surviving plants to detect the expression of bar gene which encodes for phosphinothricin acetyle transferase and confirmed herbicide resistance in transgenic plants.